The impact of the COVID-19 pandemic on the well-being, work conditions, and education of early career psychiatrists in the WHO Eastern Mediterranean Region: study protocol - Hosseini, Seyedeh Reihaneh; Hajebi, Ahmad; Shalbafan, Mohammadreza; Ghannadi, Farnaz; Larnaout, Amine; Nofal, Marwa; Gondek, Tomasz M.; Pinto da Costa, Mariana (Frontiers in Psychiatry, 2024)
Background: The COVID-19 pandemic placed great strain on healthcare professionals, leading to a substantial resulting in significant impact and a redistribution of the workforce redistribution. Despite the active involvement of the Eastern Mediterranean Region Office (EMRO) and the World Health Organization (WHO) actively involvement in managing mental health crises, there is a knowledge gap concerningregarding the working conditions and training opportunities available for early career psychiatrists (ECPs) during the pandemic period.Objectives: This study aims to investigate the impact of the COVID-19 pandemic on ECPs, and how it affected their well-being, employment, and educational opportunities.Methods: A mixed methods study has been conducted in Iran, Egypt, and Tunisia, three EMRO member countries. It includesencompassed a cross-sectional survey with self-reported questions, and a qualitative study with individual in-depth interviews.Discussion: The findings of this study will raise awareness to the working conditions of ECPs within the EMRO region and its member societies, both during the COVID-19 pandemic and beyond. The results will serve as a basis for encouraging supervisors and policymakers and supervisors to mitigate the pandemic's impact on psychiatric training, strengthening healthcare systems' preparedness, and equipping early career psychiatrists with the necessary skills to deal with the mental health consequences of the COVID-19 pandemic.